ANALYSIS OF SCIENTIFIC APPROACHES TO DEFINING THE ESSENCE OF THE REGION'S INTELLECTUAL CAPITAL - LALUEVA, Nadiya (Herald of Khmelnytskyi National University. Economic sciences, 2023)
Based on the analysis of literary sources of Ukrainian and foreign authors, a number of scientific approaches to the definition of the concept of "intellectual capital of the region" are considered. Among them are: structural, functional-structural, terminological, resource, practical, and reproduction of new value. The peculiarities of the definitions of the essence of intellectual capital are generalized. The analysis allowed the author to form his own vision of the essence of the intellectual capital of the region, which is defined as a set of accumulated and qualitative knowledge, abilities, intellectual resources that can create added value and ensure the effective development of the region's economy. It is substantiated that most scholars focus their attention on the study of intellectual capital as an intangible asset of an organization, a set of employees' knowledge, intellectual assets, abilities that have economic value and generate income. The economic aspects of the study of intellectual capital are substantiated. It is stated that the structure of intellectual capital is quite complex, which is due to the multidimensionality of its formation, use and management.The general structure of intellectual capital is formed. The ways of structuring intellectual capital are highlighted. Having studied different opinions of scientists on the structure of intellectual capital in the region, the following elements of it are allocated: human (personal) capital, organizational (structural) capital and social capital.It is proved that the intellectual capital of the region is the basis of the productive forces of modern society and the main resource for the strategic development of regions in the knowledge economy.
Keywords: intelligence; intellectual capital; region; knowledge; human capital; social capital; organizational capital; intangible assets; knowledge economy